Update of the Fishes of Mangrove and Coastal Waters of Northeastern Langkawi - V.C, Chong,; , Y.P, Ng; B.J, Hairi; A.L, Ooi,; L.L, Chew,; M, Amirah; B.N, Affendi (Malaysian Journal of Science, 2005)
Two fish surveys in the waters of Langkawi’s northeastern mangroves and adjacent nearshore waters were carried out in August 2003 and April 2004, to provide further information of the fish diversity that was first reported in the Langkawi Scientific and Heritage Expedition, April 2003. To date, there are 91 species of fish belonging to 42 families recorded inside mangrove-fringed estuaries and coastal inlets. Five new families, the Belonidae, Elopidae, Lobotidae, Pristigasteridae and Ostraciidae, have been added to the previous record of 37 families. In the open nearshore waters, from Pulau Peluru Strait to off Gua Cherita, 50 fish species were recorded. Cluster analysis indicates that the fish communities of Sg. Kisap, Sg. Kilim and coastal inlets were more similar to each other, than to Sg. Ayer Hangat or the open nearshore waters. However, half of the fish species present in the open nearshore waters also occur inside the mangrove-fringed estuaries and waterways. It is proposed that ecological linkages between the inshore waters, mangroves and coral reefs exist, involving fish movements for maturation/ spawning, feeding and utilization of the coastal habitats as nursery areas.